Discursos sobre o crack: análise das representações sociais de usuários, familiares e profissionais do CAPS - Silva, Naiara França da (2013)
Due to the speed at which the crack has earned place in society and because it has been considered, nowadays, a major social problem, this work aimed to analyze the social representations assigned to the users of crack and its use in the perspective of users, their families and health professionals. The study was conducted according to the referential of the Theory of Central Core. The survey was conducted in four CAPS, where thirty crack users, twenty relatives and thirty health professionals were interviewed. Data collection used an interview with evocative questions. The data were organized and processed by the EVOC software and the socio demographic data were analyzed by the software SPSS. In the group of users, the most significant representations regarding crack relate to the issue of dependency, as well as in the group of relatives, although using different terms. In turn, health professionals held to the motivation for the consumption and the consequences that this use entails. It was found that the groups, in general, define crack as a drug that destroys the person in various spheres of life and is highly addictive. About inductive term crack users, the most significant representations concern the care, focusing on the need of assistance this user has, given that its destructive power hinders its abandonment. However, there were some specifics among groups. The results indicate the hopelessness of users finding support from people to confront this drug. Similarly, the family presented negative evocations, although not directed to the user, but to changes in the family caused by the problems arising from the use of crack. In professional discourses, the difficulty in daily contact with these users prevailed, which limit its work with them. It was noted, finally, the absence of changes prospect with regard to the future of crack users between the groups and a noticeable disbelief in relation to their recovery. These results indicate important concerns, such as the challenges faced by health professionals concerning their performance against the dependence of the crack and the difficulties of treatment and prevention measures. Therefore, it is expected that this study provides support for establishing future studies in social psychology and mental health, and the creation of new shares that increase attention to these users, as well as their adherence to treatment.